Intertextual Analysis of A.S. Pushkin’s «I Remember a Wonderful Moment…»: on the Controversy about the Addressee - Mkrtchyan, Marianna (Bulletin of Yerevan University H: Russian Philology, 2025)
The article is devoted to the intertextual analysis of Pushkin’s poem «To***» («A Magic Moment I Remember…») based on its comparison with the other poems by Pushkin and with the works of V.A. Zhukovsky, who is the author of the famous line «The genius of pure beauty». The generally accepted addressee of the poem is A.P. Kern, although this version has been repeatedly questioned. The Empress Elisaveta Alexeevna is increasingly named as the addressee. This version has been expressed many times, but for the first time we have considered it from the standpoint of the intertextual approach. The analysis of the image of the beloved, lexical structure of the several poems by Pushkin and intersections of their themes and motives, and also the features of the poet’s work on the text drafts shows that the poem «To***» can be put in one row with other works that form a certain unity together and are united by the same addressee. These include «To her», «The Oak groves, where in the silence of the freedom...», «To N.Ya. P<lyuskova>», «At the beginning of my life I remember school...»). In turn, the line «The genius of pure beauty» borrowed by Pushkin from Zhukovsky introduces into the text of the poem a whole set of additional implicit meanings that do not fit into the version about Kern as its addressee. The analysis of both poets’ texts, one more time insistently shows the necessity to review to whom the poem was addressed, as well as, to include the second version into textbooks and tutorials.